The Characteristics of Mount Kerinci Climbers Kayu Aro Sub-District Kerinci Regency - Alzikri, R. Flourenta; Erianjoni, Erianjoni; Afdhal, Afdhal (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
In 2014 the highest number of visitors was from the archipelago and abroad. In the following year the number of visitors has decreased from 2014. If allowed to continue the number of visitors from year to year will decrease, certainly this Mount Kerinci attraction will not be glimpsed again by the tourists. This study was to determine the characteristics of mountain climbers based on travel, socio-demographic, psychographic and geographical characteristics. This type of research is quantitative descriptive. The research subject was mountaineer Mount Kerinci. The sampling technique uses incidental sampling of 98 people. Data collection techniques using questionnaires, observations and documentation. Data analysis techniques use percentages. Research results: 1). Travel characteristics: generally climber visit 2 days, the average visit on weekends / Sundays, on average aiming for recreation and pleasure, on average tourists need accommodations such as homestays. 2). Socio-demographic characteristics: generally the age of climber is 18-20 years, the majority of men, mostly unmarried, are mostly high school education levels with the average work of students. 3). Psychographic characteristics: on average using motorbikes, most of them get information from friends, on average because they enjoy a panoramic view of the beautiful scenery, most climber are satisfied, on average think first to return, generally the first time to Mount Kerinci. 4). Geographical characteristics: the average originated and lived in the Jambi area.